Examining contextual control in roulette gambling. Issue 1 (4th December 2014) - Whiting, Seth W.; Dixon, Mark R.
Abstract We examined the influence of derived rules on roulette betting. Twelve college students selected between red and black bets on a roulette wheel in a pretest, then participated in a relational training procedure that established functions of more than for the color bet least often and less than for the color bet more frequently. When playing roulette again, 11 of the 12 participants increased betting on the color with the same formal properties of the contextual cue for more than in relational training.